Civil wars : internal struggles, global consequences - Olson Lounsbery, Marie (Canada : University of Toronto Press, 2009)
What motivates individuals to take up arms against their government? What types of states have historically been more prone to internal conflicts? In Civil wars: internal struggles, global consequences Marie Olson Lounsbery and Frederic Pearson explore these questions and present a comprehensive analysis of the causes, consequences, and management potential regarding civil wars throughout the world.
Civil war in the contemporary era -- The causes of civil war: individual and group analysis -- State-level factors leadign to civil war -- International effects on civil wars -- Conflict processes during civil wars -- The resolution of civil wars -- The aftermath of civil war.
Includes bibliographical references (p. 229-245) and index.
Keywords: Civil war; Insurgency; Guerra Civil; Insurgencia